2002
DOI: 10.1128/aem.68.3.1040-1046.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin-Like Activity of Butyrivibrio fibrisolvens JL5 and Its Effect on Other Ruminal Bacteria and Ammonia Production

Abstract: When ruminal bacteria from a cow fed hay were serially diluted into an anaerobic medium that had only peptides and amino acids as energy sources, little growth or ammonia production was detected at dilutions greater than 10 ؊6 . The 10 ؊8 and 10 ؊9 dilutions contained bacteria that fermented carbohydrates, and some of these bacteria inhibited Clostridium sticklandii SR, an obligate amino acid-fermenting bacterium. Phylogenetic analysis indicated that the most active isolate (JL5) was closely related to Butyriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Besides all the efforts to characterize bacteriocins produced by ruminal bacteria, until now only three lantibiotics (butyrivibriocin OR79A, butyrivibriocin AR10, bovicin HC5), four class II bacteriocins (lichenin, bovicin 255, enterocin BC25, enterocin CCM4231), and two class III bacteriocins (enterolysin, albusin B) have been identified or at least partially characterized at the biochemical and genetic levels among strains of ruminal bacteria (10,15,16,18,19,21,(35)(36)(37). Moreover, although the occurrence of c Frequency refers to the proportion of the time that clusters containing the specified protein with a particular domain were identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides all the efforts to characterize bacteriocins produced by ruminal bacteria, until now only three lantibiotics (butyrivibriocin OR79A, butyrivibriocin AR10, bovicin HC5), four class II bacteriocins (lichenin, bovicin 255, enterocin BC25, enterocin CCM4231), and two class III bacteriocins (enterolysin, albusin B) have been identified or at least partially characterized at the biochemical and genetic levels among strains of ruminal bacteria (10,15,16,18,19,21,(35)(36)(37). Moreover, although the occurrence of c Frequency refers to the proportion of the time that clusters containing the specified protein with a particular domain were identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptide production has been detected from several GI bacteria, both gram-negative and gram-positive (Miranda et al 1993;Leer et al 1995;Kalmokoff and Teather 1997;Avelar et al 1999;Yildirim et al 1999;Gomez et al 2002;Rychlik and Russell 2002). This strongly suggests AMPs have a role in altering and coordinating the GI bacterial community, although the exact nature of this role is not yet known.…”
Section: Quorum-sensingmentioning
confidence: 99%
“…Also, the inhibitory effect of nisin on some GI bacteria (Rada and Dlabal 1998;Mantovani and Russell 2001) suggests it has an inhibitory role in the GI tract. Ruminal isolates of Streptococcus bovis are sensitive to a bacteriocin produced by Enterococcus (Morovskyl et al 1998), and many gram-positive bacteria are sensitive to a peptide produced by Butyrivibrio fibrisolvens (Rychlik and Russell 2002). Also, the addition of nisin to an artificial rumen altered the fermentation pattern, which included increasing propionate and decreasing butyrate production (Jalc and Lauková 2002).…”
Section: Quorum-sensingmentioning
confidence: 99%
“…[3][4][5] In recent years, they have been isolated from the rumen bacteria Streptococcus bovis and Butyrivibrio fibrisolvens. [6][7][8][9] Both predominant cellulolytics and readily isolated from ruminants, Ruminococcus albus 8 has been shown to produce bateriocin to inhibit the growth of Ruminococcus flavefaciens when co-cultured on cellobiose. 10) Fatty acids and surfactants have enhanced the growth performance and cellulytic activity of Ruminococci.…”
mentioning
confidence: 99%
“…10) Previous studies have suggested that the chemical character and inhibition mechanism of bacteriocin vary among different strains of the same species bacteria. 2,18) Although many studies of bacteriocins from rumen bacteria have focused on their effects on rumen fermentation, [6][7][8][9]18) much fewer data are available concerning the antimicrobial activity of rumen bacteriocin as to other gut flora. The purpose of this study was to investigate the characteristics of the bacteriocin from R. albus 7 in detail and to examine its potential use as an alternative to antibiotics for pathogenic bacteria.…”
mentioning
confidence: 99%